The Existence of the Constitutional Court in Examining the Law on Ratification of International Treaties Against the 1945 Constitution - Geofani Milthree Saragih; Diana Octavia Situmeang (Eastasouth Institute, 2022)
The Constitutional Court is one of the state institutions in Indonesia that has an important role in upholding the Indonesian constitution. One of the most influential authorities is the judicial review of the law against the 1945 Constitution. In Indonesia itself, international ratifications and international agreements, if they have been recognized and will be adjusted in national law, will be promulgated in one form of law as stated in Article 9 paragraph (2) of Law Number 24 of 2000 concerning International Agreements. In relation to the judicial review authority possessed by the Constitutional Court, this study will examine the extent to which the Constitutional Court based on its authority has reviewed the law on the ratification of international treaties. The research method used in this study is normative with a library study approach that is associated with various laws and regulations related to the topic. This study confirms that the Constitutional Court in examining the law on the ratification of international treaties is very rare because of the small number of applications received. But basically, the Constitutional Court has the authority to examine the law on the ratification of international treaties against the 1945 Constitution.